Synthesis of Hexagonal Gold Nanoparticles and Study of its Optical and Near-field Distribution Properties by Discrete Dipole Approximation. Issue 1 (1st January 2022) - Ge, Linlin; Tang, Junqi
Abstract: Anisotropic nanostructures with unique physical and chemical properties have been widely applied in optical, electronic, magnetic, and catalytic fields. This paper described the synthesis of hexagonal gold nanoplates (HAuNPs) by trisodium citrate and ascorbic acid. The optical and near-field distribution properties of hexagonal gold nanoplates were studied by discrete dipole approximation method. Simulation results showed that due to the shape anisotropy of HAuNPs, the optical properties of HAuNPs were significant differences between the horizontal orientation and vertical orientation.